Late Roman glazed pottery from Rifnik near Celje - Bausovac, Maja; Pirkmajer, Darja (Rei Cretariae Romanae Fautorum Acta, 2012)
Rifnik near Šentjur lies to the east of Celje and is one of the better known late Roman settlements in Slovenia since archaeological excavations have been carried out here for several decades. On account of its height and steep slopes, Rifnik offered a safe refuge to its inhabitants, and with its dominant position on the margin of the Kozjansko hills, it commands the broad valley of the Voglajna River, where in Roman times one of the ancillary roads from Celeia ran towards the north-east.